A simple synthesis of new quinoxaline-bisquinoline hybrids linked via thiomethyl ether - Banda Padma; Praveen Kumar Rathod; Panaganti Leelavathi (The Bioscan, 2025)
A straightforward synthesis of new hybrid molecules comprising two important pharmacophores, quinoline and quinoxaline is presented. The hybrid molecules were synthesized in a convergent manner from S-alkylation of quinoxaline-2,3-dithiol with 2-chloro-3-(chloromethyl) quinolines. Quinoxaline-2,3-dithiols were accessed from 2,3-dichloroquinoxaline and thiourea. The other component quinolines were obtained from of 2-chloro-3-formyl quinolines by reduction and subsequent chlorination to corresponding chlorides. The designed strategy for target hybrids is simple with broad substrate scope and good yields.